MILITARY COUPS AND MILITARY REGIMES IN AFRICA - Japhet, M. (Scientia Militaria - South African Journal of Military Studies, 2012)
Growth of Military States As late as 1961 the African image had not been tarnished to any great extent by the incidence of military coups. Indeed, a field study tour conducted in 1960- 1 - the year of independence as it has been called - to investigate the place of the armed forces in societies in Africa did not provide the evidence on which to forecast the eventual spate of coups. Togo was the first country in West Africa to experience a military coup when on 13 January 1963 Togolese soldiers, recently demobilised from the French colonial armies and facing unemployment as a result of refusal of their applications to join ’the miniscule Togolese army, staged an armed coup that led to the assassination of President Sylvanus Olympio. At the time Africa’s reaction to the coup in Zaire was one of severe disapproval, manifested by vociferous verbal attacks on the junta and international ostracism of the new government until it had legitimated itself through national elections. This can be seen to be largely motivated by the insecurity many civilian governments in Africa were experiencing and was to some considerable extent intended to be an object lesson to aspiring military commanders. At the same time the Organisation for African Unity discussed proposals covering measures to prevent the spread of coups or the legitimation of military regimes, however no common policy was produced.